Strategies to Minimize the Application of Grammar Translation Methods in Cambodian English Classrooms: Why is it Special? - Chin, Pisith; Em, Sereyrath; Chau, Linn; Seng, Sacha; Pen, Dina (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This article aims to provide academic strategies that English teachers in Cambodia can use to reduce their reliance on grammar translation methods (GTM) in their classrooms. Recognizing the limitations of GTM and their potential negative impact on students' language proficiency, this article emphasizes the importance of applying teaching techniques and alternative teaching methods to improve learning outcomes in English. The article offers a series of practical recommendations, including task-based learning (TBL), communicative language teaching (CLT), and learner-centred approaches (LCA), to promote interactive and active language learning environments. These strategies encourage active participation, meaningful communication, and authentic language use, helping students develop their full English proficiency. Besides, the article highlights a new indication of why the mentioned methods are suitable for implementation in the Cambodian context. The article also sheds light on future research. Therefore, future studies can address the challenges of applying the mentioned techniques using quantitative and qualitative methods.